TensorFlow machine learning projects : build 13 real-world projects with advanced numerical computations using the Python ecosystem /: build 13 real-world projects with advanced numerical computations using the Python ecosystem. (2018) - Jain, Ankit; Fandango, Armando; Kapoor, Amita
No abstract available